1988
DOI: 10.1902/jop.1988.59.5.332
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Genetic Model Testing in Early Onset Periodontitis

Abstract: Familial aggregation of early onset or juvenile Periodontitis (JP), a disorder that varies in expression and age of onset, has been recognized for some time. Autosomal recessive and X‐linked inheritance patterns have been suggested, and one large pedigree has demonstrated autosomal dominant inheritance. The variability and age limitations in clinical phenotypic diagnosis present several problems to genetic analysis, because information on members of the youngest and older generations may be lost to the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…This variability in presentation of significant signs of disease makes diagnosis difficult, not only in declaring if a patient suffers from the disease but also in detecting patients who do not suffer from the disease and differentiating between adult and aggressive forms of periodontitis. The problems associated with the clinical differentiation of periodontal disease are not uncommon in medical genetics, since similar problems arise in the study of other delayed-onset hereditary traits [133]. …”
Section: Risk Characteristicsmentioning
confidence: 99%
“…This variability in presentation of significant signs of disease makes diagnosis difficult, not only in declaring if a patient suffers from the disease but also in detecting patients who do not suffer from the disease and differentiating between adult and aggressive forms of periodontitis. The problems associated with the clinical differentiation of periodontal disease are not uncommon in medical genetics, since similar problems arise in the study of other delayed-onset hereditary traits [133]. …”
Section: Risk Characteristicsmentioning
confidence: 99%
“…When the original pedigrees were analyzed redressing for ascertainment bias, they were found to be supportive of autosomal inheritance of EOP (Hart et al, 1992). Both autosomal-recessive inheritance (Saxen and Nevanlinna, 1984;Beaty et al, 1987;Boughman et al, 1988Boughman et al, , 1992 and autosomal-dominant inheritance (Boughman et al, 1986;Marazitta et al, 1991) of early-onset periodontitis are supported by existing data. In the largest study to date (100 families), Marazitta and colleagues (1994) found the strongest evidence for an autosomal-dominant susceptibility gene, with 70% penetrance.…”
Section: Family Studiesmentioning
confidence: 79%
“…This variability in presentation of significant signs of disease makes diagnosis difficult, not only in declaring if a patient suffers from the disease but also in detecting patients who do not suffer from the disease, and differentiating between adult and aggressive forms of periodontitis. The problems associated with the clinical differentiation of periodontal disease are not uncommon in medical genetics, since similar problems arise in the study of other delayed-onset hereditary traits (Boughman et al, 1988;Potter, 1989).…”
Section: (B) Familial Aggregationmentioning
confidence: 99%
“…Huntington's chorea is another example of a hereditary disease where the diagnosis is possible only relatively late in life (OMIM 143100). The problems of genetic model testing in aggressive periodontitis (AgP) have been highlighted by Boughman et al (1988), who noted that AgP has a variable age of onset and is often not recognized until after puberty, that the upper age limit of expression of the disease is curtailed (artificially by a diagnostic definition that loss of attachment in patients older than 35 years is attributable to chronic periodontitis), and that difficulties exist in acquiring periodontal disease histories in edentulous family members.…”
Section: (B) Familial Aggregationmentioning
confidence: 99%